An Analytical Study of the Strategic Flexibility Variation as a Function of the Dynamic Capabilities Based on Supply Chain Management (Case Study: The General Petroleum Products Distribution Company in Baghdad) - Hussam Ali Mhaibes (International Journal of Supply Chain Management, 2018)
Abstract- This paper represents an advanced contribution to explore the nature of the dynamic capabilities based on supply chain management in the oil distribution company as a vital field within Iraq and how to activate these capabilities in achieving Strategic flexibility, drawing on past experiences and literature in establishing a scientific and field basis for this company. The purpose behind this paper is to introduce a new understanding of the concept of dynamic capabilities based on supply chain management and whether it is possible to adopt advanced capabilities in management and the possibility of applying them in an Iraqi company and what is their role in achieving strategic flexibility. This concept was clarified through a framework to learn more about how these concepts work. The study has been conducted in the General Petroleum Products Distribution Company (Baghdad) drawing upon a research sample of the company's leaders (directors of managements and departments) within the company. It consists of 33 out of 56 directors. The study adopts the questionnaire method in data collection including four dimensions of dynamic capabilities (capability of sensing, learning, integrating and marketing) based on supply chain management and three dimensions for the variability of the strategic flexibility (marketing flexibility, productivity, and competitivity). The study uses a set of statistical tools based on the SPSS 23 and EXCELL 2013 programs to measure the description and diagnosis of the sample, the variables of the research, the measurement of the correlation and the effect of the different tools. The study reaches a set of conclusions, the most important of which is that the multi-dimensional dynamics model affects the achievement of the strategic flexibility within the company and to varying degrees of dimensions. Keyword: strategic Flexibility, Variation, Dynamic Capabilities, Supply Chain Management, Company.